Pengaruh Word Of Mouth terhadap Keputusan Pembelian Pada Toko Warren Store di Kota Palopo - Rahmat Hidayat; Nurul Aulia Rahma; Erwin; Carles; Hairil Abd Hajar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to explain the influence of word of mouth communication on purchasing decisions. The type of research used is associative research with a quantitative approach. The population of this study were consumers of the Warren Store in Palopo City who already bought based on word of mouth information with 30 respondents as a sample that randomly taken. Data obtained with a questionnaire in the form of a Likert scale. From the results of simple regression estimation, it can be seen that word of mouth communication has a positive and significantly correlated with purchasing decisions, so to encourage consumer purchasing decisions, the Warren Store should design and make sure the information has directly spread by former consumers with certain incentives through social media..